Design of Three-Phase Three-Switch Buck-Type Rectifier for Pre-Charging Application - Anandh S; Vijayan S; Paramasivam Paramasivam (Institute of Advanced Engineering and Science, 2016)
The main objective of a pre-charging circuit in variable frequency drives is to pre-charge the DC-bus capacitor without any voltage and current overshoot within the specified time. In exisiting variable frequency drives seperte pre-charging circuits (or) thyristor bridges were used due to this drives power density, cost becomes high and control technique becomes complex. This paper presents about the design of three-phase three-switch buck-type rectifier for pre-charging application used in variable frequency drives which elimates the disadvantages of existing techniques. In this paper we will discuss about design procedure of pre-charging circuit of an 800KW converter with dc-link output voltage of 775V at an input ac voltage of 550V, 60Hz, selection of power and passive components, voltage and current stress of power transistors. In the final this paper discusses about loss distribution of the components and comparison of new converter technique with existing pre-charging techniques.